2016
DOI: 10.3892/mmr.2016.4887
|View full text |Cite
|
Sign up to set email alerts
|

Silybin suppresses cell proliferation and induces apoptosis of multiple myeloma cells via the PI3K/Akt/mTOR signaling pathway

Abstract: Abstract. Silybin is a biologically active component extracted from the seeds of Silybum marianum, which has been shown to have inhibitory effects on prostate, skin, bladder, lung and colon cancer cells, in addition to its efficacy in the treatment of liver diseases, including hepatitis and cirrhosis. The aim of the present study was to investigate whether silybin suppresses the proliferation and induces apoptosis of multiple myeloma (MM) cells and to elucidate its molecular targets. The proliferative and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Previous reports have demonstrated that silibinin inhibits mTOR pathway in both renal cell carcinoma and multiple myeloma cells [ 45 47 ]. Here, we showed that silibinin inhibited the phosphorylation of mTOR, p70S6K, and 4E-BP1 in human glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that silibinin inhibits mTOR pathway in both renal cell carcinoma and multiple myeloma cells [ 45 47 ]. Here, we showed that silibinin inhibited the phosphorylation of mTOR, p70S6K, and 4E-BP1 in human glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, further study showed that Silybum marianum was associated with a trend towards significant reductions in liver toxicity in children with ALL with liver toxicity [ 39 ]. In MM cells, silibinin has been demonstrated to be useful in the treatment of MM via inhibition of proliferation and an increase in apoptosis via inhibiting PI3K/Akt-mTOR signaling pathways [ 37 ]. These are emerging new ways of silibinin usage which may be promising therapeutic interventions for the treatment of β-TM, AML, ALCL, and MM.…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin has, however, been demonstrated to exert anti-multiple myeloma efficacy. Silibinin inhibition of cellular proliferation and increased apoptosis via repression of PI3K/Akt-(mammalian target of rapamycin) mTOR signaling have been recently reported to occur in U266 MM cells [ 37 ].…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…Alterations of signaling pathways are important in the regulation of multiple cellular functions of lung cancer, including cell growth and proliferation (21)(22)(23)(24). A previous study by Zhu et al confirmed that the AKT signaling pathway is involved in the intrinsic apoptosis of non small-cell lung cancer cells (25).…”
Section: Discussionmentioning
confidence: 99%